Estimation of Height from Foot Measurement in Kalaburagi District - Sunilkumar C.A; Santosh Garampalli (Institute of Medico-legal Publications Pvt Ltd, 2021)
Estimation of height of a person plays an important role in identification of a person which is necessary incriminal cases and as well as in mass disasters where only a portion or a part of body may be seen. The presentstudy was carried out on the measurement of foot length and body height of 342 students (170males and172 females) of 05 to 30 years of age. Anthropometric measurements were taken by using anthropometricinstruments in centimeter to the nearest millimeter. All the measurements were taken in a well lighted room.Obtained data was analysed for correlation coefficient and to derive a regression formula betweenfoot length and height of an individual. A medium correlation of height was observed with foot length andit was statistically significant. The present study would be useful for anthropologists and forensic experts